Explosive boiling of nano-liquid argon films on high temperature platinum walls: Effects of surface wettability and film thickness - Wang, Yan-Hong; Wang, Shao-Yu; Lu, Gui; Wang, Xiao-Dong (International journal of thermal sciences, 2018)
Because of scaling effect, phase change behaviors of nano-liquid films on solid surfaces display distinct features from macroscale pool boiling. In this work, evaporation and explosive boiling of nano-liquid argon films with various film thicknesses on hydrophilic or hydrophobic platinum surfaces are investigated via molecular dynamics simulations. The simulations show that the onset of explosive boiling closely depends on the film initial thickness on both the hydrophilic and hydrophobic surfaces, and the onset temperature for explosive boiling significantly reduces with the increase of the film thickness. In addition, the simulations also demonstrate that, with the same film thickness and the same wall superheat, explosive boiling is triggered on the hydrophilic surface, while only evaporation is observed on the hydrophobic surface, indicating that a high surface wettability reduces the onset temperature, which is opposite to the prediction by classical nucleation theory and the observation in pool boiling experiments. For a thicker film and a higher surface wettability, it is found that a larger temperature gradient is generated along the film thickness direction due to the heat accumulation effect, which leads to a very high temperature occurring at the film bottom and thereby is responsible for the lower onset temperature for explosive boiling on these circumstances. •Phase change behaviors of nano-liquid films on high temperature walls were studied.•Effects of surface wettability and film thickness on phase change were revealed.•Onset temperature for explosive boiling was found to be lower for thicker films.•Onset temperature for explosive boiling reduces as the wettability improves.